Harmonization of Mudharabah Contracts: Study of DSN-MUI Fatwa, Compilation of Sharia Economic Law (KHES), Legislation and Its Application in Indonesian Sharia Banking (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2023)
The mudharabah contract is identical to the profit-sharing scheme in Islamic banking operations. However, in practice, murabahah contracts are widely used by Islamic banking, so mudharabah contracts and profit-sharing schemes inherent in Islamic banking should be widely used in each of their product offerings. Therefore, this study discusses mudharabah contracts from a regulatory perspective and practices in Islamic banking. This research is a sharia economic law research that uses a descriptive method of literature, with the primary data source being the Fatwa of the National Sharia Council of the Indonesian Ulama Council (DSN-MUI) and laws and regulations. This type of research is qualitative research with three stages of data analysis, namely data condensation, presenting data, and drawing conclusions. The results of this study indicate that the statutory regulations (laws, POJK and PBI) that support the position and application of mudharabah contracts in Islamic banking originate from the substance of the DSN-MUI Fatwa regarding mudharabah contracts. This shows that there is a harmonization of regulations and also the practice of implementing mudharabah contracts in Islamic banking. The position of mudharabah contracts that are widely used by Islamic banks in carrying out their functions, namely collecting funds, channeling funds with financing schemes, and providing services for certain products, strengthens and makes the existence of Islamic banks as financial institutions that apply profit-sharing schemes.